초음파추출과 열수추출에 의한 민들레의 항산화 및 지질강하 효과 - 양하영(Ha Young Yang); 이선구(Seon Goo Lee) (동의생리병리학회지, 2011)
This study was conducted to investigate the effects of dandelion (Teraxacum platycarpum) extracts obtained by only water and with ultrasonification on antioxidative system and lipid metabolism in high cholesterol-fed rats. Five groups of rats were given high cholesterol diets for 8 weeks. The control group received without dandelion extracts and the other four groups received with one of dandelion extracts for 4 weeks respectively ; TP-N-1(100 mg/kg/day of Teraxacum platycarpum water extract), TP-N-2(200 mg/kg/day of Teraxacum platycarpum water extract), TP-S-1(100 mg/kg/day of Teraxacum platycarpum water-ultrasonification extract), TP-S-2(200 mg/kg/day of Teraxacum platycarpum water-ultrasonification extract). The results are summarized as follows; The hepatic and plasma TBARS levels significantly decreased in the dandelion extracts groups compared to those of no treatment group. Especially the group TP-N-2 was comparatively best among those. TP-N-2 groups had significantly higher levels of glutathione peroxidase (GSH-Px) and catalase activities. There was no significant difference between dandelion extracts groups and no treatment group in SOD levels. In plasma triglyceride level, plasma FFA level, TP-S-2 group had significantly lower levels than that of the other groups. In plasma glucose levels, dandelion extracts group were similar to those of normal rats. Plasma total cholesterol levels significantly decreased in the TP-S-2 group compared to those of the other groups. HDL levels were also significantly higher than those of the other groups. Compared with those of no treatment group, dandelion extract groups had significantly higher levels of LDL. In liver total cholesterol level, TP-S-2 groups had significantly lower levels than that of the other groups. Compared with those of no treatment group, dandelion extracts groups had significantly lower levels of liver triglyceride, but especially the TP-S-2 group showed comparatively the best significant effect among those. TBARS, triglyceride, LDL, FFA levels significantly decreased in TP-S-2 groups compared to the other four groups. HDL levels was also significantly higher than the other four groups. According to the above result, it could be suggested that ultrasonic extraction have the upper hand in lipid metabolism and water extraction have the advantage of antioxidative system.